Transcript availability dictates the balance between strand-asynchronous and strand-coupled mitochondrial DNA replication. Issue 20 (20th September 2018) - Cluett, Tricia J; Akman, Gokhan; Reyes, Aurelio; Kazak, Lawrence; Mitchell, Alice; Wood, Stuart R; Spinazzola, Antonella; Spelbrink, Johannes N; Holt, Ian J
Abstract: Mammalian mitochondria operate multiple mechanisms of DNA replication. In many cells and tissues a strand-asynchronous mechanism predominates over coupled leading and lagging-strand DNA synthesis. However, little is known of the factors that control or influence the different mechanisms of replication, and the idea that strand-asynchronous replication entails transient incorporation of transcripts (aka bootlaces) is controversial. A firm prediction of the bootlace model is that it depends on mitochondrial transcripts. Here, we show that elevated expression of Twinkle DNA helicase in human mitochondria induces bidirectional, coupled leading and lagging-strand DNA synthesis, at the expense of strand-asynchronous replication; and this switch is accompanied by decreases in the steady-state level of some mitochondrial transcripts. However, in the so-called minor arc of mitochondrial DNA where transcript levels remain high, the strand-asynchronous replication mechanism is instated. Hence, replication switches to a strand-coupled mechanism only where transcripts are scarce, thereby establishing a direct correlation between transcript availability and the mechanism of replication. Thus, these findings support a critical role of mitochondrial transcripts in the strand-asynchronous mechanism of mitochondrial DNA replication; and, as a corollary, mitochondrial RNA availability and RNA/DNA hybrid formation offer means of regulating the mechanisms of DNA replication in the organelle.